2009
DOI: 10.1016/j.neuroimage.2008.10.030
|View full text |Cite
|
Sign up to set email alerts
|

Regional white matter volume differences in nondemented aging and Alzheimer's disease

Abstract: Accumulating evidence suggests that altered cerebral white matter (WM) influences normal aging, and further that WM degeneration may modulate the clinical expression of Alzheimer's disease (AD). Here we conducted a study of differences in WM volume across the adult age span and in AD employing a newly developed, automated method for regional parcellation of the subcortical WM that uses curvature landmarks and gray matter (GM)/WM surface boundary information. This procedure measures the volume of gyral WM, util… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
244
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 278 publications
(256 citation statements)
references
References 93 publications
11
244
0
1
Order By: Relevance
“…Given that AD and vascular brain injury are commonly co-morbid (Sonnen et al 2009), it is possible that earlier findings of lower FA in AD patients reflected vascular disturbances as opposed to a specific effect of AD pathology. Salat et al (2009) described an AD-specific decline in WM volume in the parahippocampal and entorhinal cortices, regions that traditionally suffer from atrophy with AD. Longitudinal scans that contrasted subjects with stable MCI and those that converted to AD showed increased WM atrophy in the temporal lobe (Davatzikos et al 2011).…”
Section: Wm and Alzheimer's Diseasementioning
confidence: 99%
“…Given that AD and vascular brain injury are commonly co-morbid (Sonnen et al 2009), it is possible that earlier findings of lower FA in AD patients reflected vascular disturbances as opposed to a specific effect of AD pathology. Salat et al (2009) described an AD-specific decline in WM volume in the parahippocampal and entorhinal cortices, regions that traditionally suffer from atrophy with AD. Longitudinal scans that contrasted subjects with stable MCI and those that converted to AD showed increased WM atrophy in the temporal lobe (Davatzikos et al 2011).…”
Section: Wm and Alzheimer's Diseasementioning
confidence: 99%
“…Specifically, volumetric reductions have been reported in the medial temporal and prefrontal regions of the human brain (Kramer et al 2007;Fjell and Walhovd 2010;Raz et al 2010;Cardenas et al 2011). Age-related white matter changes also have been reported in frontal and temporal regions of the human brain (Davis et al 2009;Salat et al 2009;Murray et al 2010;Ziegler et al 2010). These structural changes in gray and white matter have been associated with age-related cognitive decline (Kramer et al 2007;Fjell and Walhovd 2010;Murray et al 2010;Ziegler et al 2010;Cardenas et al 2011).…”
mentioning
confidence: 93%
“…In grey matter, the trajectory of these age-related changes is variable across the brain such that more rapid decline is observed in regions of the frontal and parietal lobes than in the temporal and occipital lobes (Fjell et al, 2013;Kennedy & Raz, 2009;Raz et al, 2004Raz et al, , 2005Resnick et al, 2000;Resnick et al, 2003;Walhovd et al, 2005Walhovd et al, , 2011. In white matter, some studies have reported a more diffuse pattern of volumetric reductions across the brain with age (Fjell et al, 2013;Resnick et al, 2000Resnick et al, , 2003Salat et al, 2009;Walhovd et al, 2005Walhovd et al, , 2011, whereas others have reported greater reduction in frontal lobe white matter compared to other regions (Brickman et al, 2006;Ferreira et al, 2014;Head et al, 2004).…”
Section: Introductionmentioning
confidence: 99%